CONDUCTING QUALITY CULTURE IN EDUCATIONAL INSTITUTIONS - Hardianto, Hardianto (SCAD Independent, 2019)
A good quality of educational institutions is very important nowadays. Currently, there are many educational institutions that are not qualified by considering from grade of national education. It is still low. In addition, there are some basics schools, high and university that have not been accredited or achieved grade C. The lack of education institutions will lead to rising unemployment and crime. In addition, the nation's competitiveness will also be low in facing global competition. To improve good quality of educational institutions, it needs to work high and state a commitment together. The existence of a good quality of educational institutions can be seen from the improvement of culture, structure, access, systems and relationship with stakeholders. Management of human resources in educational institutions is also a key quality of the educational institution.